PENGARUH PELATIHAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. MAHA JAGAD PERKASA DENPASAR - Ni Kadek Dwi Indah Oktaviani; Nyoman Mustika; Sapta Rini Widyawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
Increasingly fierce competition requires companies to improve employee performance. Employee performance has an important role in achieving the goals of a company. Because with good employee performance, company goals can be achieved optimally. Based on the results of initial observations, the problems that exist at PT. Maha Jagad Perkasa Denpasar is a decrease in the level of employee performance can be proven through the level of employee absenteeism. Lack of training, motivation and work discipline. This research was conducted at PT. Maha Jagad Perkasa Denpasar using a population and a sample of 30 employees as research respondents. Data collection is done through observation, interviews, and documentation. The data analysis technique used in this study was multiple linear regression analysis which was processed using SPSS version 25. Based on the results of the analysis, this study shows that training, motivation, and work discipline have a positive and significant effect on employee performance at PT. Maha Jagad Perkasa so that the better the training, motivation, and work discipline of employees in the company, the performance at PT. Maha Jagad Perkasa Denpasar.